Persepsi Pengelolaan Zakat Pertanian di Kalangan Petani Kelapa Sawit di Mamuju Tengah Perfektif Fikih Islam dan Undang-Undang Zakat - Karmila, Nini; Alimuddin, Alimuddin; Ahmad, Helmy Fauzy (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to analyze the community's understanding of the management of zakat mal among palm oil farmers in Batuparigi Village, Tobadak Sub-district, Central Mamuju Regency. Using a qualitative approach, this research focuses on an in-depth understanding of the social, cultural, and economic contexts that influence the management of zakat mal among palm oil farmers. This approach was chosen because it provides flexibility in exploring the community's understanding, attitudes and perceptions more comprehensively. Data were collected through two main methods: in-depth interviews and participatory observation. After the data were collected, data processing was conducted through thematic analysis steps. First, interviews were recorded and transcribed to ensure the accuracy of the information. Next, the transcribed data and observation notes were read in depth to identify the main themes that emerged. The researcher then categorized the information based on themes, such as understanding of zakat, challenges in management, and socio-economic impact of zakat. The results show that the majority of oil palm smallholders have a limited understanding of the obligation of zakat mal, especially regarding the mechanism of its calculation and distribution in accordance with sharia. Factors such as education level, access to information, and guidance from local zakat institutions play a significant role in shaping this understanding. Despite the awareness of the importance of zakat, many farmers do not understand how to calculate the nisab and haul of agricultural zakat, especially palm oil zakat. From the perspective of fiqh schools of thought, there are different interpretations of agricultural zakat that affect practices in the field. This contributes to the discrepancy between the theory of zakat in fiqh and its implementation among farmers. Analysis of the Zakat Law No. 23/2011 shows that socialization and education related to mal zakat still need to be improved, so that palm oil farmers better understand their obligations.